Pengaruh Intellectual Capital Dan Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan Perbankan Yang Terdaftar Di BEI Periode 2018-2021 - Feri Wahyudi; Widowati; Baiq Desthania Prathama (Akuntabel: Jurnal Ilmiah Akuntansi, 2024)
This research aims to determine the effect of intellectual capital which is proxied by VAICTM and good corporate governance which is proxied by the audit committee on company performance which is proxied by Return On Assets (ROA). The population in this study were banking companies listed on the Indonesia Stock Exchange in 2018-2021 using a purposive sampling technique using the criteria of banking companies that published financial reports in 2018-2021. The data analysis technique used in this research uses multiple linear regression analysis. The results of this research show that partially intellectual capital as proxied by VAICTM has an effect on company performance. Meanwhile, good corporate governance as proxied by the audit committee has no effect on company performance. The results of this research also show that the independent variables, namely intellectual capital and good corporate governance, are able to influence the dependent variable, namely company performance, by 32.4%, while the remaining 67.6% is influenced by other variables not used in this research.